Tradução e adaptação do Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) para a língua portuguesa e a efetividade do treino de habiidades comportamentais para qualificar profissionais - Martone, Maria Carolina Correa (Universidade Federal de São Carlos, 2017)
The Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) authored by Mark Sundberg provides a systematic assessment for children with autism and similar delays and has become a frequent tool among those who gives consultations in this área. Divided into five components, the VB-MAPP evaluates samples of the child’s verbal repertoire from 170 developmental milestones presented in three levels (0 -18 months, 18-30 months and 30-48). The aim of this study was to translate and adapt the VB-MAPP to the Portuguese language and propose a way to qualify professionals to implement it properly. Study 1 translated and adapted to Portuguese Chapters 1 to 6 and the corresponding protocol scoring form. Study 2 tested the effect of a Behavioral Skill Training to improve the performance of the professionals in conducting the VB-MAPP. Items from a list of skills were used to measure the performance of each participant in specific tasks (Level 1, 2 and 3) of this assessment tool. The study consisted of three phases: pretest, training and posttest. Ten participants were divided into two groups: control and experimental. Both groups performed the pretest and posttest, but the training was only mandatory for the experimental group. In the pretest phase all participants received the Portuguese version of The VBMAPP and had to assess one child each. Training phase was composed of a BST package (instruction, modeling, reharsal and feedback). Only Level 1 and 2 tasks were taught. Both groups repeated the assessment in the posttest phase, however, the experimental group had an additional task: implementing the Level 3 tasks of the VB -MAPP. Still in the posttest phase, two participants (P3 and P6), presenting lower overall performances than the other participants of the experimental group, were selected for five additional posttest sessions. The results showed that all participants in the experimental group developed skills to implement The VB-MAPP regarding Level 1 and 2 tasks. About the performance of the experimental group in Level 3 tasks, it was possible to say that generalization occurred for some, but not all behaviors. The results were higher than the pretests, but lower when compared to the Level 1 and 2 tasks. Among the factors that may have contributed to this partial result we highlight: (1) Level 3 tasks are more complex than the Levels 1 and 2 and may require evaluators with more experience (2) only some milestones were selected for Level 3 testing and not all of them. As for participants P3 and P6, after a total of six posttest viii sessions, they maintained the percentage of correct answers higher than 90% for Level 1 and 2 tasks and 85% for Level 3 tasks.
Translation and adaptation of The Verbal Behavior Milestones Assessment and Placement Program (VB-MAPP) to the Portuguese language and the effectiveness of a Behavioral Skills Training package to qualify professionals
Keywords: VB-MAPP; Avaliação comportamental; Comportamento verbal; Autismo; Behavioral assessment; Verbal behavior; Autism; CIENCIAS HUMANAS::PSICOLOGIA